Enhancing Flood Preparedness: The Influence of Students’ Knowledge and Experience - Puspitasari, Hana Rifky; Khotimah, Nurul (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
Flood disasters often occur in Mentarang Hulu sub-district, Malinau Regency, North Kalimantan. The risk of flooding can be reduced if the community has knowledge and experience related to flood disasters. The purpose of this study was to determine the effect of students' knowledge and experience in dealing with flood disasters. This type of research is descriptive quantitative. The sampling technique used was purposive sampling, and a sample size of 80 students from elementary, junior high, and high school levels. Data collection techniques used observation, interviews, and documentation. The data collection instrument used a questionnaire. While the data analysis technique used descriptive statistics. The results of the study showed that the knowledge of elementary, junior high, and high school students about flood disasters was included in the GOOD category. This can be interpreted that most elementary, junior high, and high school students have good knowledge about floods. The percentage obtained was elementary school students of 85%, junior high school students of 81%, and high school students of 90%. These results also show that the experiences of elementary, junior high, and high school students about flood disasters are included in the GOOD category